The Role of the Vegetative Part in Some Plant Species to Uptake and Accumulate Lead Element from Polluted Air (an Applied Study in Baghdad /Karkh in Iraq) - Khayoon, Noor A.; Al-Salman, Ibrahim Mahdi A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The current study was conducted to test the efficiency of the vegetative part (plant leaves) of plant species of shrubs and trees involved in forming semi-artificial vegetation in the city of Baghdad, Karkh, in the uptake and accumulating the lead element that pollutes the air in the city atmosphere. Five plant sampling sites were selected: Al-Kadhimiyah, Al-Mansour, Al-Ma’aml (Al-Salam district), Al-Adl, and Al-Ameriya district intersections (Al-Seklat), and symbols were given (A, B, C, D, E) respectively. The spread and distribution of plants vary in terms of human activities and pollution levels, affecting the five sites that recorded more than 20 species. For a real comparison between plant efficiency and the effect of the nature of the region, species of recurrent and non-recurring shrubs and trees were selected in their presence at the study sites and included (Conocarpus lancifolius, Ziziphus spina christi, Eucalyptus sp., Albizia lebbeck), and non-recurring (Nerium oleander, Dodonaea viscosa, Phoenix dactylifera, Olea europaea, Myrtus communis, Ficus nitida, Citrus aurantium). The study’s results showed a variation in the ability of plant species in lead accumulators. The first site of the plants (Conocarpus lancifolius, Ziziphus spina christi, Albizia lebbeck, Eucalyptus sp., Nerium oleander, Dodonaea viscosa, Phoenix dactylifera, Olea europaea, Myrtus communis, Ficus nitida, and Citrus aurantium) was recorded at (0.46, 0.56, 0.36, 0.55, -, 0.68, -, -, 0.33, 0.29, 0.84) respectively. The second site of the same plants was (0.74, below the detection limit, 0.25, 0.57, -, -, 0.16, -, -, 0.31, -) respectively. The third site was (0.95, 0.65, 0.832, 0.831, 0.86, 1.02, -, -, -, 0.436, -, 0.532), respectively. The fourth site was (0.34, 0.95, 0.48, 0.40, -, 0.19, -, -, -, -), respectively. The fifth site was (0.48, 0.50, 0.49, 0.41, -, -, -, 1.45, -, -, -, -) ppm, respectively. The current study was conducted from October 2021 to May 2022